Role of immunoglobulin g (igg) from the induction of escherichia coli pili adhesion protein isolated from infertile male semen with 32.2 kda molecular weight as opsonin and anti-adhesion an in vitro escherichia coli infection - Sukarjati, Sukarjati; Amilah, Susie (Folia Medica Indonesiana, 2017)
Escherichia coli (E. coli), a major cause of male genital tract infections, is asymptomatic and may result in male infertility. We have succeeded in isolating and characterizing proteins of E. Pili coli isolates from semen of infertile men who function as adhesin with a molecular weight (MW) 32.2 kDa. This study aims to prove the ability of IgG results adhesion proteins induced pili of E. MW coli 32.2 kDa as opsonin to determine the value of the activity and phagocytic capacity and as an anti- adhesion by calculating the average number of E. coli that attached to human spermatozoa. E. coli infertile men's semen were cultured using standard bacteriology. Peritoneal macrophages were isolated from mice. Spermatozoa from donors were prepared using Sil with Select Plus. IgG was obtained from mice immunized with (1) PBS (control), (2) E. coli pili adhesion protein isolated from infertile men semen with MW of 32.2 kDa and (3) weakened E. coli isolated from infertile men's semen. Phagocytic activity value was determined by counting the number of cells activated macrophage phagocytosis process in 100 cells. Phagocytic capacity value was determined by counting the number of bacteria ingested by 25 macrophages. Anti-adhesion test was done by counting the number of bacteria attached to 100 spermatozoa. The results of this study showed difference (p=0.000) in phagocytic activity and phagocytic capacity (p=0.000) between treatment (1) and (2), and between treatment (1) to (3). However, treatment (2) and (3) did not differ neither in phagocytic activity (p=0.693) nor in phagocytosis capacity (p=0.125). Anti-adhesion test produces difference (p=0.000) in the number of E. coli that attached to human spermatozoa between treatments (1) and treatment (2), and between treatments (1) and (3). The number of E. coli that attached to human spermatozoa between treatment (2) and treatment (3) was not significantly different (p=0.371). In conclusion, IgG from the induction of E. coli pili adhesion protein of infertile men semen isolates with MW of 32.2 kDa can increase phagocytic activity and capacity as well as serve as an anti- adhesion. Thus, IgG from the induction of E. coli pili adhesion protein of infertile men semen isolates with MW of 32.2 kDa is protective against in vitro E. coli infection, so that it can be used as material to prevent male reproductive tract infections due to E. coli.